Phenotypic and genetic aspects of production in the Dohne Merino. IV. The influence of age of the ewe on production lambs - Fourie, A.J.; Heydenrich, H.J. (1983)
To determine the influence of the age of the ewe on characteristics such as body mass, greasy fleece mass, clean fleece mass, fiber diameter and staple length the data obtained from 500 ewes born between 1970 and 1979 was used. Their body mass at mating increased from 55 kg to 61 kg between the ages of 1½ and 5½ years, after which it declined steeply to the age of 9½ years. Greasy fleece mass increased up to the age of 3½ years (4.53 kg) and then steadily declined up to the age of 9½ years (2.82 kg). In contrast, maximum clean fleece mass was achieved at the age of 1½ years (2.94 kg). Clean fleece mass declined by 17.5% from 1½ to 9½ years of age. Fiber diameter increased from 21.4 to 23.3 microns between the age of 1½ and 7½ years after which it declined up to the age of 9½ years. The staple length was 92.2 mm at 1½ years of age followed by a linear decline up to 9½ years of age.